Communicating Resistance to the Banality of Online Crime Through Advertising - Cosmas Gatot Haryono; Rowena Capulong Reyes (Komunikator, 2024)
Many Indonesians remain unaware of the perils of cybercrime and often perceive it as an inherent risk of engaging with social media platforms. Exploiting societal negligence and carelessness, criminals target individuals with alarming frequency. BCA, through its recent advertisement titled “Don’t Know, Give No!”, has introduced a novel approach to bank advertising in Indonesia. Researchers are intrigued by the discourse of resistance against online crime that BCA Bank seeks to foster through these advertisements. Employing qualitative methods informed by Van Dijk’s critical discourse analysis, this study delves into the nuanced strategies employed by BCA. The findings illuminate BCA’s endeavor to construct a discourse resisting the normalization of cybercriminal activities. BCA endeavors to encourage the public to fortify their digital defenses by adopting prudent and conscientious social media practices, advocating for a thoughtful approach prior to any online action. In this digital epoch, the responsibility for safeguarding personal data transcends traditional banking realms, with customer security becoming contingent upon individual actions and choices.